RANCANG BANGUN APLIKASI EVALUASI KINERJA KARYAWAN BERBASIS WEB DENGAN SIMULASI DATA DAN PENDEKATAN FUZZY MCDM - Wilson Sah Putra Halawa; Hotma Pangaribuan (LPPM Universitas Putera Batam, 2026)
Employee performance evaluation is an essential activity in manufacturing industries to maintain productivity and product quality. Conventional evaluation methods are often subjective and less effective when performance assessment involves multiple criteria and uncertain data. This study aims to design and implement a web-based employee performance evaluation system using the Fuzzy Multi-Criteria Decision Making (Fuzzy MCDM) method. Employee performance is assessed based on two main criteria: work quantity, measured by production output against dynamic targets, and work quality, measured by the number of defective products. The Fuzzy MCDM approach is applied through fuzzification, weighting, aggregation, and defuzzification processes to produce objective and adaptive performance scores. The system is developed using PHP and MySQL for data processing, while HTML, CSS, JavaScript, and Chart.js are used for interface design and performance visualization. The results show that the system is able to calculate performance scores accurately and present evaluation results clearly through graphical representations. The proposed system can support effective performance monitoring and data-driven managerial decision-making in manufacturing environments.